2014
DOI: 10.1007/s00330-014-3543-9
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer staging with extracapsular extension risk scoring using multiparametric MRI: a correlation with histopathology

Abstract: • Multiparametric MRI is an accurate diagnostic technique for preoperative prostate cancer staging • ECE risk scoring predicts extracapsular tumour extension at final pathology • ECE risk scoring shows an AUC of 0.86 on the ROC-curve • ECE risk scoring shows a moderate inter-reader agreement (K = 0.45) • Multiparametric MRI provides essential knowledge for optimal clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 35 publications
3
53
0
3
Order By: Relevance
“…7 Using ROC curve analyses, the accuracy of the ESUR ECE-score (AUC=0.82, Figure 1) for harboring extraprostatic disease was comparable to recent publications, thus demonstrating that standardized reading of mpMRI has the potential to predict EPE accurately. 23 Our results of the ECE-score were comparable to Boesen et al and…”
Section: Discussionsupporting
confidence: 94%
“…7 Using ROC curve analyses, the accuracy of the ESUR ECE-score (AUC=0.82, Figure 1) for harboring extraprostatic disease was comparable to recent publications, thus demonstrating that standardized reading of mpMRI has the potential to predict EPE accurately. 23 Our results of the ECE-score were comparable to Boesen et al and…”
Section: Discussionsupporting
confidence: 94%
“…While some authors suggest few patients with cT3 disease are candidates for NVB preservation, 7 the incorporation of multi-parametric magnetic resonance imaging (MRI) to preoperative staging has challenged this paradigm, as recent studies have confirmed that MRI can identify extraprostatic extension (EPE) to a better extent than trans-rectal ultrasound and/or digital rectal examination. 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the presence of ECE was based on clinical parameters such as PSA, biopsy Gleason, and the extent of cancer involvement at biopsy [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Although specific prediction nomograms have been built and validated for this aim [4][5][6], none of them included apparent diffusion coefficient (ADC) from diffusionweighted imaging (DWI) to predict ECE.…”
Section: Introductionmentioning
confidence: 99%